An Evaluation of Hemoglobin A1c Monitoring at a Student-Run Free Clinic in Kansas City, Missouri - Murali, Madhavi; Bodepudi, Alaya; Casubhoy, Imaima; Kraemer, Edwin (Journal of Student-Run Clinics, 2021)
Background: The hemoglobin A1c is critical for monitoring and managing type II diabetes and providing clinicians with a framework for a treatment plan. Our study analyzes compliance to the American Diabetes Association (ADA) standards of appropriate A1c monitoring and encourages other clinics to monitor the same information within their own clinics. Methods: A retrospective chart review was conducted on all patients who visited the Sojourner Health Clinic between January 2017 and November 2019. All patients who had met the criteria for A1c screening based on recommendations from the ADA were included in the study, as well as patients who were charted as diabetic or pre-diabetic. A total of 88 patients met the criteria for this study. Data collected included patient documentation as diabetic or pre-diabetic and patientsâ€™ three most recent A1c values with corresponding dates. Based on this data, these patients were categorized as diabetic, pre-diabetic, or non-diabetic, and were evaluated on whether their A1c was monitored at appropriate intervals. Results: A total of 21.6% of patients were monitored appropriately for their diabetic status determined by their A1c values. Only 18.2% of diabetic patients were accurately monitored. Patients with an unknown diabetic status had the lowest rate of appropriate monitoring. Conclusions: Most patients at the Sojourner Health Clinic are not properly monitored for diabetes using the clinic’s modified A1c monitoring guidelines. The clinic can make several improvements to strengthen adherence to these guidelines with the implementation of new protocols for better A1c monitoring. Further studies should be made to assess the efficacy of these changes.